Practicality of E-Module Utilizing Meta-Creative Strategies - Rahmiati, Rahmiati; Putri, Mutia; Saputra, Indra; Astuti, Murni; Miga Dewi, Siska (The Indonesian Journal of Computer Science, 2023)
This study aims to create an e-module for beauty and makeup research. It places its focus on evaluating the practicality of the e-module through the utilization of the meta-creative strategy approach. This evaluation is carried out by assessing it with two distinct groups, which are lecturers and students. The outhor employs a systematic approach in evaluating the e-module with the meta-creative strategy. The primary criteria for assessment include ease of media usage, time efficiency, interpretation ability and equvalency. The analysis results indicate a high level of practicality for the e-module with meta-creative strategy used in this learning process. The lecturer and students both rated it highly, with scores of 0,92 and 0.87 respectively. These score reflect the favorable reception from both groups of stakeholders. These findings lend support to the concept of meta-creativity e-module developments and underscore the potential of educational technology in enhancing the learning experience.